2015
DOI: 10.2147/jbm.s65556
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of human T-cell lymphoma/leukemia virus type-1 (HTLV-1) antibodies among blood donors at Enugu, Nigeria

Abstract: BackgroundHuman T-cell lymphotrophic/leukemia virus (HTLV-1) is a retrovirus implicated in transfusion-transmitted infection.ObjectiveThe objective of this study was to determine the seroprevalence of HTLV-1 antibodies among blood donors at the University of Nigeria Teaching Hospital, Enugu, Eastern Nigeria.MethodsA cross-sectional study was carried out on consented participants over 4 months. A total of 300 blood donors were recruited consecutively from the blood bank. The serum of the collected 5 mL of blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Durojaiye et al 5 found 0.5% prevalence among blood donors in 2014, while Yuguda et al 10 reported 3.2% in 2017 without confirmatory assays. Okoye et al 1,6 showed prevalence rates of 0.5% and 0%, respectively, in South-East. Zero prevalence has also been reported previously in Nigeria 11 and cases of dual infection with both HTLV-1 and -2 have also been reported in Nigeria.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Durojaiye et al 5 found 0.5% prevalence among blood donors in 2014, while Yuguda et al 10 reported 3.2% in 2017 without confirmatory assays. Okoye et al 1,6 showed prevalence rates of 0.5% and 0%, respectively, in South-East. Zero prevalence has also been reported previously in Nigeria 11 and cases of dual infection with both HTLV-1 and -2 have also been reported in Nigeria.…”
Section: Introductionmentioning
confidence: 94%
“…Human T-lymphotropic viruses 1/2 (HTLV-1/2) are primate T-lymphotropic viruses and members of the deltaretroviruses, which include simian T-cell leukaemia virus (STLV) and bovine leukaemia virus. 1 In about 7% of the infected individuals, HTLV-1 is the aetiological agent of an aggressive lymphoproliferative malignancy known as adult T-cell leukaemia/lymphoma (ATLL), as well as HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP), a neurological disorder associated with increased lymphoproliferation. It is also associated with a host of other diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation